Analyses of the failures on shear cutting blades after trimming of ultra high-strength steel. (January 2017) - Son, Dongmin; Kim, Hoyoung; Kang, Jun-Yun; Yun, Hyo Yun; Lee, Jae-Jin; Park, Soon Keun; Lee, Tae-Ho; Lee, Jehyun
Abstract: Damages on shear cutting blades were analyzed after 50, 000 strokes of trimming on an ultra high-strength steel sheet. Traditional D2 alloy and an advanced one (Cr08H) based on the composition of 1C-8Cr were quenched from 1030 °C, tempered at 180 °C and submitted to the shear cutting test. Cr08H had lower hardness, a smaller volume fraction of M7 C3 carbides while it contained a larger volume fraction of retained austenite. And these resulted in more scratches and rounded edges because of degraded resistance to wear and local plastic deformation. In spite of higher impact toughness, Cr08H exhibited inferior resistance to chipping which was the consequence of localized brittle fracture. It could be concluded that this was caused by more transformation of austenite as well as by insufficiently hardened matrix, both of which were attributed to inappropriate conditions of the heat treatment. Highlights: Two types of cold-work tool steels were compared in shear cutting of steel sheets. Insufficient hardness with less carbide led to more wear and plastic deformation. Excellent impact toughness did not ensure the resistance to chipping. Instability of retained austenite contributed to the development of chipping.